2021
DOI: 10.1111/ors.12652
|View full text |Cite
|
Sign up to set email alerts
|

Poor dental health in British Army Infantry recruits reduces their quality of life: A cross‐sectional survey and retrospective analysis of health records

Abstract: Introduction: Oral Health Related Quality of Life (OHRQoL) is a determinant of an individual's wellbeing and can be affected by dental disease. For military recruits, adverse OHRQoL may result in poor performance, and has safety implications. The aim of this study was to determine the incidence of dental extractions and dental health of a sample of new infantry recruits.Method: Electronic healthcare recordings of tooth extraction incidence was compared to recruits from the general military population. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies have investigated the impact of acute dental pain on OHRQoL, most of which have included small numbers of participants or used tools which incompletely explored OHRQoL (Almoznino et al, 2015; Cimilli et al, 2012; Currie et al, 2015; Edwards et al, 2022; Shueb et al, 2015). Currie 2015 undertook the most comprehensive study to date, finding diseases of the pulp and associated periapical disease (symptomatic irreversible pulpitis, symptomatic apical periodontitis and acute apical abscess) were the most common and impactful reasons for urgent dental care (UDC) attendance (Currie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the impact of acute dental pain on OHRQoL, most of which have included small numbers of participants or used tools which incompletely explored OHRQoL (Almoznino et al, 2015; Cimilli et al, 2012; Currie et al, 2015; Edwards et al, 2022; Shueb et al, 2015). Currie 2015 undertook the most comprehensive study to date, finding diseases of the pulp and associated periapical disease (symptomatic irreversible pulpitis, symptomatic apical periodontitis and acute apical abscess) were the most common and impactful reasons for urgent dental care (UDC) attendance (Currie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Orofacial pain can impact patients in several ways, including time off work, the use of pain‐relieving medication, ability to care for dependants, loss of sleep, difficulties eating and talking (Almoznino et al, 2015; Currie et al, 2015; Edwards et al, 2022). Not only does this result in negative functional and societal impact, but several of these will also result in personal financial costs for patients, such as the use of medication, requirement for additional childcare, time away from work, travel and the cost of an emergency appointment.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that 39% of Army recruits at 18 years old had the literacy level of an 11-year-old,10 compared with 15% of adults in the general population 11. Army recruits typically have poor previous dental attendance, with a recent internal report finding only 22% attended regularly prior to enlistment 12…”
Section: Introductionmentioning
confidence: 99%
“…Military personnel exhibit high disease levels on enlistment. In 2014, 64% of recruits at the Infantry Training Centre Catterick were found to have active caries compared with a prevalence of 30% of the general population 1 12. A survey of dentists treating military patients found that 62% believe that new recruits identified as suffering significant dental anxiety should not be allowed to join the armed forces 9.…”
Section: Introductionmentioning
confidence: 99%